2013
DOI: 10.1007/s11832-013-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Management pitfalls of fractured neck of femur in osteogenesis imperfecta

Abstract: Introduction Fractured neck of femur in osteogenesis imperfecta is rarely reported. Its management is always difficult because of bone fragility and the outcome is not well known. We, therefore, aimed to study the management pitfalls in this group of patients. Methods We retrospectively reviewed five cases of fractured neck of femur in four patients treated in our hospital between 2006 and 2009. The demographic data, mode of injury, fracture configuration, treatment, complications, clinical and radiological ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 30 publications
(38 reference statements)
0
35
0
Order By: Relevance
“…Although femur fractures are common in OI patients, no literature specifies fracture and non-union incidence in adults, most likely explained by the rarity of this disease [6][7][8]. Non-union rate is expected to be higher in OI adults than non-OI adults, as surgical treatment is more challenging due to anatomical and bone-related abnormalities [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although femur fractures are common in OI patients, no literature specifies fracture and non-union incidence in adults, most likely explained by the rarity of this disease [6][7][8]. Non-union rate is expected to be higher in OI adults than non-OI adults, as surgical treatment is more challenging due to anatomical and bone-related abnormalities [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…23 However, fractures of the femoral neck are relatively uncommon in patients with osteogenesis imperfecta. 19,23,24 Surgical stabilization of femoral neck fractures is challenging because of low bone mineral density or obstruction by hardware from previous…”
Section: Femoral Neck Fracturesmentioning
confidence: 99%
“…fracture fixation, specifically the presence of femoral intramedullary hardware that was used for stabilization of the femoral shaft in pediatric patients with osteogenesis imperfecta. 19 Chow et al 24 reported the management of femoral neck fractures in 2 adults with osteogenesis imperfecta. The first case involved a 22-year-old woman who sustained a femoral neck fracture and a supracondylar fracture of the distal femur.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…There are additional factors that complicate surgical management in this patient population including poor bone quality, difficult radiographic visualization of the proximal femur secondary to deformity and severe osteoporosis, small patient size, and the frequency of preexisting implants. [6] Within our institution, we report three cases of femoral neck fractures that occurred in patients with OI, and describe a technique of improving fluoroscopic visualization of proxi-mal femoral anatomy in patients with severe osteopenia.…”
Section: Introductionmentioning
confidence: 99%